1994
DOI: 10.1080/01690969408402129
|View full text |Cite
|
Sign up to set email alerts
|

Structure and meaning in the verb lexicon: Input for a syntax-aided verb learning procedure

Abstract: How might children learn the meanings of new verbs? Well-known problems with unconstrained induction of word meanings from world observations suggest that additional sources of information are required. This paper presents an investigation of the availability of syntactic cues to verb meaning. If there exist strong and reliable parallels between verbs' structural and semantic properties, then each verb's linguistic context could provide valuable evidence about its meaning. In Experiments 1-3, adult subjects' j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
1
31
1
1
Order By: Relevance
“…It is more likely that children were using the limited lexical-semantic information present in the sentences to construct meaning. It has been shown that children can deduce the meanings of unknown verbs based on knowledge about other semantic and syntactic information in the sentence (Gleitman & Gillette, 1999;Naigles, 1990Naigles, , 1996Naigles & Hoff-Ginsberg, 1995;Fisher, 1994;Fisher, Gleitman, & Gleitman, 1991;Landau & Gleitman, 1985), as well as morphological markers on the verbs (e.g., Behrend, Harris, & Cartwright, 1995). Our children might have generated expectations about what words should occur after the pseudoverb based on their interpretations of the pseudoverbs.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that children were using the limited lexical-semantic information present in the sentences to construct meaning. It has been shown that children can deduce the meanings of unknown verbs based on knowledge about other semantic and syntactic information in the sentence (Gleitman & Gillette, 1999;Naigles, 1990Naigles, , 1996Naigles & Hoff-Ginsberg, 1995;Fisher, 1994;Fisher, Gleitman, & Gleitman, 1991;Landau & Gleitman, 1985), as well as morphological markers on the verbs (e.g., Behrend, Harris, & Cartwright, 1995). Our children might have generated expectations about what words should occur after the pseudoverb based on their interpretations of the pseudoverbs.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown using a variety of tasks (e.g., Naigles, Gleitman, & Gleitman, 1992;Gropen, Pinker, Hollander, Goldberg, & Wilson, 1989) that children are sensitive to the meaning associated with particular syntactic forms. We aim to demonstrate here (along with Fisher, 1994;Naigles and Terrazas, 1998) that adults are also sensitive to this relationship. Second, we demonstrate that the meaning conveyed by particular syntactic forms is not due to previously learned lexical items (especially verbs) that may occur in these sentences.…”
Section: The Indexical Hypothesismentioning
confidence: 99%
“…Evidence for this comes from studies in which novel verbs are used in diVerent constructions (e.g., Fisher, 1994;Kaschak & Glenberg, 2000). For example, Kaschak and Glenberg (2000) presented participants with sentences that had innovative denominal verbs (i.e., verbs that are created from nouns).…”
Section: Verb Constructionsmentioning
confidence: 99%